Analisis Indeks Kepuasan Masyarakat Pelanggan PDAM Tirta Mahakam Cabang Tenggarong - Sugeng Raharjo; Heru Suprapto (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:In line with the policy and regulations on Public Services, PDAM Tirta Mahakam needs to improve the quality of services and make continuous improvements so that PDAM Tirta Mahakam can perform its duties and roles in improving service quality.To find out more about the commitment of PDAM Tirta Mahakam in providing public services for clean water supply, a survey was needed that can provide an overview of the public perception of PDAM Tirta Mahakam customers. The results of the survey are expected to provide assistance to programs to improve services and improve clean water services.Respondents in this study were households that were registered as customers of PDAM Tirta Mahakam Tenggarong Branch until early 2019. Sampling was carried out proportionally by considering the distribution of respondents in the working area of PDAM Tirta Mahakam Tenggarong Branch. The population was based on the number of Household Connections (SRs) with a sample size of 375 respondents spread in 13 Urban Vilalges in Tenggarong District taken proportionallyThe results of the study explained that based on the Service Element, the Satisfaction Index of the Tirta Mahakam Tenggarong Branch scored 2,942. This value means that the service performance of PDAM Tirta Mahakam Tenggarong Branch is categorized as Low Service Performance. There is one service element that has good performance, namely the service element from Product Specifications with a value of 3.165 while for the other eight elements it is not good. Based on the Urban Village, only four stated that their performance was good, namely Timbau, Loa Ipuh, Mangkurawang and Panji. Eight urban villages have low service performance. One other has poor service performance, namely Loa Ipuh Darat.Based on important performance analysis, the attributes that need to be improved are due to high customer expectations, namely the smooth flow of the day, the accuracy of office service hours, the accuracy of bills with water usage, the suitability of bill costs with water quality, conformity with ability to pay, the quality of raw water, and clarity water.Keywords : Service quality; Consumer Satisfaction Index; PDAM services; Important Performance Analysis